The therapeutic effects of thalidomide and etanercept on septic rats exposed to lipopolysaccharide - Ilhan, Nevin; Susam, Solmaz; Gul, Huseyin Fatih; Ilhan, Necip (Turkish Assoc Trauma Emergency Surgery, 2019)
BACKGROUND: The aim of this study was to evaluate the therapeutic effects of thalidomide and etanercept on lipopolysaccharide (LPS)-induced sepsis in a rat model. METHODS: Thirty male Wistar Albino rats were divided into 5 groups: Control, LPS, LPS+ Thalidomide, LPS+ Etanercept, and LPS+ Thalidomide+Etanercept. The control group was given a 1 mL intraperitoneal (i.p.) injection of 0.9% saline solution. For endotoxic treatment, the rats were injected with a single i.p. dose of LPS (Escherichia coli 0111: B4 (5 mg/kg). Thalidomide (0.5 mg/kg) and etanercept (1 mg/kg) were administered i.p. to the therapeutic groups. Hepatic tissue tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), intercellular adhesion molecule-1 (ICAM-1) and platelet-derived growth factor (PDGF) levels were determined by enzyme-linked immunosorbent assay and malondialdehyde (MDA) levels and total oxidant status (TOS) were measured using appropriate methods. RESULTS: In vivo results exhibited elevated liver tissue TNF-alpha, IL-6, ICAM-1, PDGF, MDA, and TOS levels in the LPS-treated animals compared with the controls. The analysis of liver tissue supported the findings of biochemical alterations and indicated a therapeutic role for thalidomide and etanercept. Treatment of septic animals with these agents resulted in a remarkable decrease in the selected proinflammatory cytokines, angiogenic factors, and reactive oxygen parameters. CONCLUSION: Restoration of cytokine balance and oxidant status to normal levels following treatment with selected therapeutic agents suggests that thalidomide and etanercept can help to avoid the potentially devastating effects of sepsis.
Talidomid ve etanersept’in lipopolisakkarite maruz bırakılan septik sıçanlarda terapötik etkileri
Keywords: Etanercept; lipopolysaccharide; sepsis; thalidomide